The Value of Macular Optical Coherence Tomography in Watchful Waiting of Suprasellar Masses: A 2-Year Observational Study. Issue 4 (December 2021) - Jørstad, Øystein Kalsnes; Wigers, Andreas Reidar; Marthinsen, Pål Bache; Evang, Johan Arild; Moe, Morten Carstens
Abstract : Background: A possible benefit of optical coherence tomography (OCT) in the approach to tumors involving the optic chiasm may be the ability to foresee visual deterioration. This study investigated the value of OCT in watchful waiting for compressive optic neuropathy as the primary management of suprasellar masses. Methods: The research was conducted as a 2-year observational study of a patient cohort with conservatively managed mass lesions involving the optic chiasm on MRI. Threshold perimetry and macular OCT were performed at baseline and each follow-up examination. Univariate Cox regression was used to determine the effect of baseline and longitudinal covariates upon development of visual field (VF) loss compatible with chiasmal dysfunction. Results: Nineteen eyes of 19 patients were included. The optic chiasm–tumor relationship on baseline MRI was abutment in 6 cases and compression in 13 cases. Seven eyes developed VF loss. None of the baseline covariates were predictors of VF loss. The longitudinal decrease in mean macular ganglion cell complex (mGCC) thickness on OCT was 2.5 μm/yr for eyes that developed VF loss and 0.2 μm/yr for eyes that did not develop VF loss ( P = 0.02). The hazard ratio for VF loss per 1-μm/yr decrease in mGCC thickness was 1.30 (95% confidence interval [CI] 1.04–1.62; P = 0.02) for the inferior nasal quadrant and 1.45 (95% CI 1.02–2.07; P = 0.04) for the inferior temporal quadrant. Conclusions: OCT offers a valuable complement to perimetry in monitoring for compressive optic neuropathy. Longitudinal mGCC thinning can anticipate VF loss.